Le sportif en travailleur face à la lutte anti-dopage. Éléments de critique et propositions - Aubel, O.; Ohl, F. (Movement & Sport Sciences - Science & Motricité, 2016)
The fight against doping was mainly structured by a repressive and preventive approach based on a conception of the moral fault of the athlete. The article purposes is, on one hand to question the limits of this way of thinking the fight against doping and, on the other, to use a sociological perspective to reflect, thanks to the case study of cycling, on the role of sports` working conditions and employment on the use of illicit substances. This analysis of the working conditions help to sketch another way of thinking the reduction of doping risk.